2007
DOI: 10.1007/s11250-007-9119-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of adenosine deaminase activity in cattle naturally infected with Theileria annulata

Abstract: The purpose of this study was to determine serum ADA activity in cattle naturally infected with Theileria annulata. In this study, a total of 37 cross-bred cattle which 27 of it showing clinical signs of theileriosis constituted infected group and 10 healthy cattle as control group were used as animal materials. Infected group divided into three groups according to their PCV values. Cattle with PCV > or = 25 were put on group I (n = 9), those with PCV 13-24 were put on group II (n = 11) and those with PCV < or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
21
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 25 publications
(72 reference statements)
10
21
1
6
Order By: Relevance
“…In this study, the development of primarily compensated metabolic acidosis was detected in all infected animals with theileriosis, but metabolic acidosis could go into uncompensated form (lowest HCO 3 , TCO 2 , and PCO 2 compared to the other groups) in the severely anemic group. In this study, clinical findings in cattle with theileriosis were consistent with those reported by other researchers (2,3,21). As reported by others (2,3), petechial hemorrhage was observed on the planum nasolabiale and inner parts of the pinna in one patient.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, the development of primarily compensated metabolic acidosis was detected in all infected animals with theileriosis, but metabolic acidosis could go into uncompensated form (lowest HCO 3 , TCO 2 , and PCO 2 compared to the other groups) in the severely anemic group. In this study, clinical findings in cattle with theileriosis were consistent with those reported by other researchers (2,3,21). As reported by others (2,3), petechial hemorrhage was observed on the planum nasolabiale and inner parts of the pinna in one patient.…”
Section: Discussionsupporting
confidence: 93%
“…These results were parallel to those of other researchers (21,22), indicating that inflammatory responses (22) increased due to the disease or that lymphocyte proliferation (23) occurred in lymphoid organs to fight against protozoa invading the organism. There was no difference between the anemia groups as far as WBC levels concerned (24).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Reported cases of leishmaniasis and theileriasis described an increase in ADA activity in serum of infected mammals (Khambu et al, 2007;Altug et al, 2008). The reduction in ADA activity could cause an increase in extracellular concentrations of adenosine, which would be converted to inosine.…”
Section: Discussionmentioning
confidence: 99%